Have Canadian Emergency Physician Opioid Prescriptions for Undifferentiated Abdominal Pain Changed Significantly Over Five Years? - Wei, Mike; Da Silva, Marco; Perry, Jeffrey (Université d'Ottawa | University of Ottawa, 2022)
Introduction: In North America, data over the last decade have found significant morbidity associated with opioid use and prescribing of opioids to patients. The objective of our study was to assess if there has been a change in opioid prescribing practices by emergency physicians over time for undifferentiated abdominal pain. Method: A medical records review for adult patients presenting at two urban academic tertiary care emergency departments was conducted for two distinct time periods; the years of 2012 and 2017. The first 500 patients per year with a discharge diagnosis of “abdominal pain” or “abdominal pain not yet diagnosed” for each year were identified and their charts were reviewed. Data were collected regarding analgesia received in the emergency department and opioid prescriptions written. Opioids were standardized into morphine equivalent doses to compare quantities of prescribed opioids. Results: 1,000 patients were included in our study. The mean age was 42.0 years and 69.6% of patients were female. Comparing 2012 to 2017, there was a non-significant decrease in opioid prescriptions written for patients discharged from the emergency department from 17.8% to 14.4% (p=0.144). Mean opioid quantities per prescription decreased from 130.4 milligrams of morphine equivalents per prescription to 98.9 milligrams per prescription (P=0.002). There was an increase in foundational analgesia use prior to initiating opioids in the emergency department from 17.6% to 26.8% (p=0.001). There was a significant decrease in opioid use in the emergency department from 40.0% to 32.8% (p=0.018). Conclusion: Opioid prescription rates have not changed significantly over our 5-year study period. However, physicians have reduced the quantity prescribed per prescription and are using less opioid analgesia in the emergency department for abdominal pain of undetermined etiology.
Keywords: Emergency Department; Opioid; Abdominal Pain